2020
DOI: 10.1111/trf.15780
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial contamination and septic transfusion reaction rates associated with platelet components before and after introduction of primary culture: experience at a US Academic Medical Center 1991 through 2017

Abstract: BACKGROUND: The high incidence of septic transfusion reactions (STRs) led to testing being mandated by AABB from 2004. This was implemented by primary culture of single-donor apheresis platelets (APs) from 2004 and prestorage pooled platelets (PSPPs) from 2007. STUDY DESIGN/METHODS: Platelet (PLT) aliquotswere cultured at issue and transfusion reactions evaluated at our hospital. Bacterial contamination and STR rates (shown as rates per million transfusions in Results) were evaluated before and after introduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 22 publications
5
27
0
Order By: Relevance
“…Prior to the four cases in 2018, only one other case had been reported by the FDA in 2013 involving Acinetobacter species 20 . A platelet unit contaminated with Acinetobacter species that did not result in any transfusion reaction has also been reported 1 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Prior to the four cases in 2018, only one other case had been reported by the FDA in 2013 involving Acinetobacter species 20 . A platelet unit contaminated with Acinetobacter species that did not result in any transfusion reaction has also been reported 1 …”
Section: Discussionmentioning
confidence: 97%
“…These environmental conditions are very supportive of bacterial growth. Bacterial contamination has been shown in 1:1000 to 1:3000 platelet components 1–5 . The skin bacterial microflora is the primary source, and less commonly contamination is derived from enteric, oral, and respiratory flora, of which Gram negative organisms in particular can contribute to potentially devastating clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Comparable performance data for other 7-day testing approaches using culture (safety measure on Day 4 or later or large-volume delayed sampling) have either not been generated or published. 12 The updated PGDprime test represents improvement of the original PGD test in ease of use and time to detection of many bacteria, including wild-type strains reported in recent years as PLT contaminants. Rapid testing as a safety measure permits dating extension to 7 days, which has been reported to save more money than it costs in many blood centers and transfusion services.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven to detect dangerously contaminated PLTs that are released as falsely negative by early culture methods due to sampling error when the bacterial contamination is still at a very low CFU/mL level. Comparable performance data for other 7‐day testing approaches using culture (safety measure on Day 4 or later or large‐volume delayed sampling) have either not been generated or published 12 . The updated PGD prime test represents improvement of the original PGD test in ease of use and time to detection of many bacteria, including wild‐type strains reported in recent years as PLT contaminants.…”
Section: Discussionmentioning
confidence: 99%
“…The test detects bacteria at or below their relevant concentrations in platelets associated with incipient patient sepsis (threshold of toxicity). Jacobs et al [5] and Kundrapu et al [6] published retrospective studies correlating CFU/mL levels of specific bacteria found in platelets and the morbidity observed in transfused patients. Minor toxicity effects were observed at 10 4 CFU/ mL for a few bacteria while the great majority of cases with moderate to severe toxicity were correlated with bacterial loads of 10 5 -10 6 CFU/mL or greater.…”
Section: Rapid Testsmentioning
confidence: 99%